Über ein Paar Geradenkomplexse - Grincevičius, K. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: К. Гринцевичюс. Об одной паре комплексов прямых K. Grincevičius. Apie vieną kompleksų dvejetą